Group Counseling with Behavior Contract to Reduce Student Phubbing: Konseling Kelompok dengan Behavior Contract untuk Mereduksi Perilaku Phubbing Siswa - Yani, Indah; Hasibuan, Ali Daud (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The widespread use of smartphones has created new behavioral challenges among students, one of which is phubbing, or ignoring others during social interactions due to phone use. Specific Background: Previous studies showed that group counseling helps students address maladaptive behaviors, yet limited research has applied the behavior contract technique in the context of Islamic junior high schools. Knowledge Gap: Few studies have specifically tested the effectiveness of behavior contracts in reducing phubbing at MTs levels. Aims: This study aimed to examine how group counseling with behavior contracts reduces phubbing among eighth-grade students. Results: Using a quasi-experimental design with 16 participants, findings revealed a significant decrease in phubbing scores in the experimental group (from high to low category), compared to the control group. Statistical analysis confirmed meaningful differences with sig < 0.05. Novelty: The research provides new evidence of behavior contract effectiveness in addressing phubbing within the MTs school environment. Implications: The findings suggest that school counselors can adopt behavior contracts as a practical strategy to foster healthier digital behavior and improve face-to-face communication among students. Highlight Students’ phubbing behavior decreased significantly after behavior contract counseling. Group counseling sessions provided structured peer interaction and support. Behavior contracts encouraged commitment and self-control in phone use. Keyword Group Counseling, Phubbing Behavior, Behavior Contract, Student Discipline, Digital Habits